Comparison of national and international quality requirements for pears - Войцеховский, Владимир; Ребезов, Максим; Андрущенко, Антон; Орловский, Николай (SWorldJournal, 2020)
This paper analyzes the current requirements of national and international standards for pears. Analysis of the quality and range of fruits in retail chains revealed differences in marketing approaches to the sale of these products. Samples with high orga